2014
DOI: 10.1261/rna.045047.114
|View full text |Cite
|
Sign up to set email alerts
|

A Spinach molecular beacon triggered by strand displacement

Abstract: We have re-engineered the fluorescent RNA aptamer Spinach to be activated in a sequence-dependent manner. The original Spinach aptamer was extended at its 5 ′ -and 3 ′ -ends to create Spinach.ST, which is predicted to fold into an inactive conformation and thus prevent association with the small molecule fluorophore DFHBI. Hybridization of a specific trigger oligonucleotide to a designed toehold leads to toehold-initiated strand displacement and refolds Spinach into the active, fluorophore-binding conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 72 publications
(84 reference statements)
0
58
0
Order By: Relevance
“…Like proteins, RNA molecules can serve as biological catalysts and genetic regulatory elements. Examples of the latter occur naturally (18)(19)(20) and have, more recently, become the target of engineering efforts to harness RNA-based sensing through riboregulators and Spinach RNA for small molecules and target RNA sequences (21)(22)(23)(24)(25). RNA sensing for diagnostics recently took a leap forward with the development of a new class of RNA sensors called toehold switches (26).…”
Section: Whole-cell Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Like proteins, RNA molecules can serve as biological catalysts and genetic regulatory elements. Examples of the latter occur naturally (18)(19)(20) and have, more recently, become the target of engineering efforts to harness RNA-based sensing through riboregulators and Spinach RNA for small molecules and target RNA sequences (21)(22)(23)(24)(25). RNA sensing for diagnostics recently took a leap forward with the development of a new class of RNA sensors called toehold switches (26).…”
Section: Whole-cell Biosensingmentioning
confidence: 99%
“…Incorporating transcription-only gene circuits would result in simpler and faster systems. These systems could include using fluorescent Spinach RNA as a direct gene circuit reporter, Spinach RNA sensors that activate in the presence of their programmed target molecule, and Spinach.ST RNA for the detection of DNA and RNA sequences (21,22,24).…”
Section: In Vitro Diagnosticsmentioning
confidence: 99%
“…It has been demonstrated that fluorescent RNA molecules, named Spinach and Broccoli, can be employed as genetically encoded reporters for RNAimaging. 2022 Spinach and Broccoli are RNA aptamers that can bind and activate the fluorescence of small-molecule dyes, such as 3,5-difluoro-4-hydroxybenzylidene-1-trifluoroethyl-imidazolinone (DFHBI-1T). 2325 Recently, the Ellington group has successfully demonstrated that Spinach can function as a reporter in an RNA-based CHA reaction in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The complementary oligo can also be an extension of the aptamer sensor, which similarly ensures a rapid and reversible response. 93, 94 Regulation by a linked short complementary sequence results in a more sensitive assay because the apparent K d of the aptamer is less impacted than with longer complementary oligos.…”
Section: Analytical Applications Of Aptamersmentioning
confidence: 99%